The Utility of Intraoperative Contrast-enhanced Ultrasound for Immediate Treatment of Type Ia Endoleak during EVAR: Initial Experience - Bianchini Massoni, Claudio; Perini, Paolo; Fanelli, Mara; Ucci, Alessandro; Azzarone, Matteo; Rossi, Giulia; D'Ospina, Rita Maria; Freyrie, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Objectives Type Ia endoleak (EL) after endovascular abdominal aortic repair (EVAR) may be misdiagnosed at completion angiography. Intraoperative contrast-enhanced ultrasound (CEUS) may play a role in early detection and immediate treatment of type Ia EL. Methods From January 2017 to April 2018, patients treated with EVAR underwent intraoperative CEUS. After endograft deployment and ballooning, digital subtraction angiography (DSA) and intraoperative CEUS were performed in a blinded fashion. All cases of type Ia EL at DSA or CEUS were considered. Results Type Ia EL detected at intraoperative CEUS and undetected at DSA was defined in 2 patients. The former was solved with intraoperative re-ballooning; in the latter case, a Palmaz stent deployment was required. The resolution of type Ia EL was detected at intraoperative CEUS control and post-operative computed tomography angiography (CTA). In another patient, the DSA detected a type Ia EL, but intraoperative CEUS reveal a type II EL from lumbar arteries. Post-operative CTA confirm the type II EL. Conclusions The reported cases prove the clinical utility of the intraoperative CEUS, permitting the early identification of 2 type Ia EL. In addition, the intraoperative CEUS is useful in case of dubious type Ia EL at DSA, avoiding unnecessary intraoperative adjunctive procedure or post-operative CTA.